(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2018)
The aim of the work is to assess the level of social assistance expenditure in the municipality of Kołobrzeg. The time frame of work covers the years 2012-2016. The following research methods were used in the work: descriptive analysis, descriptive statistics methods, index methods. The data on the basis of which the budget analysis was carried out come from the Central Statistical Office (BDL), the Municipal Office of Kołobrzeg and the Commune Social Welfare Center in Kołobrzeg. The analysis points to an annually increase in expenditure on social assistance, especially in relation to expenses for commissioned tasks, while the number of beneficiaries using various forms of social assistance decreases.